Upregulated Expression of Cancer-Derived Immunoglobulin G Is Associated With Progression in Glioma - Wang, Guohui; Li, Haonan; Pan, Jie; Yan, Tianfang; Zhou, Huandi; Han, Xuetao; Su, Linlin; Hou, Liubing; Xue, Xiaoying (Frontiers in Oncology, 2021)
Objective: Gliomas is the most aggressive intracranial tumor taking account for the vast majority of brain tumors with very poor prognosis and overall survival. Cancer-derived immunoglobulin G (Cancer-IgG) has been found that widely expressed in many malignancies, such as breast cancer, colorectal cancer, lung cancer. And cancer-IgG could promote tumorigenesis and progression. However, the role of Cancer-IgG in glioma has not been revealed yet. Methods: We mined open databases including CGGA, TCGA and GEO to study the role of IGHG1 which encoding cancer-IgG in glioma. Differential expression of IGHG1 was carried out in GEO and TCGA database. Further, the expression in different molecular subtype was analyzed. Stratified analysis was performed by clinical features. Next, immune infiltration analysis was conducted by ssGSEA. GSEA was performed to reveal the mechanisms of IGHG1. At last, immunohistochemistry was processed to validate our findings. Results: In our study, we found that expression of IGHG1 was higher in glioma and molecular subtype with a poor prognosis. Overall survival of patients with high expression of IGHG1 is worse in stratified analysis. Immune infiltration analysis indicated that expression level of IGHG1 is positively correlated with stromal score, ESTIMATE score and immune score and negatively correlated with tumor purity. Results from GSEA and DAVID demonstrated that IGHG1 may function by phagosome, antigen processing and presentation, extracellular matrix structural constituent, antigen binding and collagen-containing extracellular matrix. Finally, immunohistochemistry assay validated our findings that patients with high expression of cancer-IgG had a poor OS and DFS. Conclusion: Cancer-IgG is a promising biomarker of diagnosis and treatment for patients with glioma.